2007
DOI: 10.1007/s10979-006-9064-6
|View full text |Cite
|
Sign up to set email alerts
|

Competence to complete psychiatric advance directives: Effects of facilitated decision making.

Abstract: Psychiatric advance directives (PADs) statutes presume competence to complete these documents, but the range and dimensions of decisional competence among people who actually complete PADs is unknown. This study examines clinical and neuropsychological correlates of performance on a measure to assess competence to complete PADs and investigates the effects of a facilitated PAD intervention on decisional capacity. N = 469 adults with psychotic disorders were interviewed at baseline and then randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…Consistent with other research (35-37), length of stay was a critical predictor of all outcomes and remained so at five years. Treatment adherence (such as medication adherence) is a primary outcome examined in the psychiatric literature, and studies have examined the role of feared loss of housing, financial leverage, and threatened hospitalization in improving adherence (38)(39)(40). Adherence is also an important outcome in chemical dependency treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other research (35-37), length of stay was a critical predictor of all outcomes and remained so at five years. Treatment adherence (such as medication adherence) is a primary outcome examined in the psychiatric literature, and studies have examined the role of feared loss of housing, financial leverage, and threatened hospitalization in improving adherence (38)(39)(40). Adherence is also an important outcome in chemical dependency treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In many jurisdictions throughout the Commonwealth and United States, however, advance care plans can be overridden by mental health legislation. Elbogen et al (2007) emphasize the importance of competence as a central prerequisite to the implementation of a PAD, with the assistance of a third party (e.g. surrogate, trained facilitator) to ensure the competency of the service user when creating a PAD giving greater validity and credibility ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another analysis from this clinical trial involved examining competence to complete PADs with a newly developed instrument that evaluates patients' understanding, appreciation, and reasoning ability applied to PADs and to specific treatment decisions contained in PADs . Elbogen et al (2007) found the manualized PAD facilitation significantly improved patients' competence to complete PADs, as well as patients' treatment decision-making capacity in general. The PAD facilitation intervention For these reasons, researchers, clinicians, and consumer-advocates have hypothesized that patients who write PADs will experience a greater sense of self-determination with respect to their mental health care (Backlar et al, 2001;Srebnik, 2004;Swanson, Tepper, Backlar, & Swartz, 2000).…”
mentioning
confidence: 90%